Enhancing Healthy Salad Dressing Quality with Inulin from Jerusalem Artichoke Powder and Calamondin Peel Essential Oil - Charoenphun, Narin; Puttha, Ratchanee; Srean, Pao; Parametthanuwat, Thanya; Wongsa, Jittimon (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
This research aimed to develop a healthy salad dressing recipe by enhancing its refreshing aroma and reducing oil content using inulin from Jerusalem artichoke and calamondin essential oils. Mixture designs were used to create six salad dressing formulas, and the optimal ratio of sunflower seed oil, egg yolk, and vinegar was found to be 65%, 20%, and 15%, respectively. The effects of partial fat replacement with Jerusalem artichoke powder were also examined. The optimal ratio of sunflower seed oil to Jerusalem artichoke powder was found to be 10:3. The lightness (L* value) decreased as the amount of Jerusalem artichoke powder increased. Quality analysis showed that the healthy salad dressing had lower energy and fat content but higher protein and total antioxidant contents when compared to the control. The effects of the addition of synthetic calamondin odor and natural calamondin odor extracted from calamondin peel on sensory evaluation were also investigated. Natural calamondin odor from calamondin peel, at 0.1%, gave the highest scores for odor and taste attributes. The findings from this study provided an alternative option for health-conscious consumers.